Effects of contract farming on production and income of sunflower farmers in Kongwa district in central agricultural zone of Tanzania - Mpeta, Daniel Fabiano (Mzumbe University, 2024)
A thesis submitted in fulfilments of the requirements for award of the Degree of Doctor of Philosophy of Mzumbe University